2021
DOI: 10.1111/jonm.13446
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, fatigue and alertness during working hours among rotating‐shift nurses in Korea: An observational study

Abstract: Aims: To determine the effects of sleep parameters and fatigue on the decline in alertness of nurses across shifts. Background: Shift work can lead to nurse fatigue owing to insufficient sleep and inadequate recovery time between shifts. Nurse fatigue has adverse effects on alertness and can affect provision of quality care. Methods: An observational study using wrist actigraphs was conducted from 2019 to 2020. Participants were 82 rotating-shift nurses who provided direct nursing care in acute hospitals in So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…Employees may suffer elevated ill mental health and fatigue when they work overtime in order to meet cultural or organizational customs or others’ expectations, whereas if employees are intrinsically motivated to engage in overtime work, they may suffer less mental health troubles and fatigue. Employees who have to engage in longer working hours beyond their intention are much more likely to experience fatigue than those who are internally willing and motivated to work long hours [ 2 , 62 ]. Additionally, undertaking overtime work due to workload puts employees in a much more stressful psychological and physical situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees may suffer elevated ill mental health and fatigue when they work overtime in order to meet cultural or organizational customs or others’ expectations, whereas if employees are intrinsically motivated to engage in overtime work, they may suffer less mental health troubles and fatigue. Employees who have to engage in longer working hours beyond their intention are much more likely to experience fatigue than those who are internally willing and motivated to work long hours [ 2 , 62 ]. Additionally, undertaking overtime work due to workload puts employees in a much more stressful psychological and physical situation.…”
Section: Discussionmentioning
confidence: 99%
“…Preceding studies have suggested that long working hours may increase the risk of various psychological problems, including stress [ 1 ], fatigue [ 2 ], psychological distress, anxiety and depression [ 3 , 4 ], as well as sleep disturbances and decreased cognitive functioning [ 5 ]. Recently, recovery from work has received more attention, and it is considered essential for maintaining health and work-life balance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they must strive to reduce overtime after night shifts and avoid climates that enforce it (e.g., by not holding training or meetings after night shifts). Shift scheduling, such as length, rotation speed, and the number of consecutive shifts, would also reduce nurse fatigue [ 49 , 50 ]. However, further research is needed on the sleep environment and individual approaches (including diet and physical activity) that enable high-quality sleep after night shifts.…”
Section: Discussionmentioning
confidence: 99%
“…The Pittsburgh Sleep Quality Index (PSQI), developed by Dr Buyee in 1989 [ 27 ], was used to assess sleep quality. This scale is currently more commonly used in psychiatric clinical assessment abroad because of its ease of use in terms of survey methods and its high correlation with the results of polysomnographic electroencephalography (EEG) tests [ 28 ]. The scale is used to evaluate the quality of sleep in the previous month and consists of 19 self-rated and 5 other-rated entries (not involved in scoring), which include 7 sub-items of subjective sleep quality, sleep latency, sleep duration, sleep efficiency, sleep disturbance, hypnotic use, and daytime dysfunction.…”
Section: Methodsmentioning
confidence: 99%